Comparative analysis of the quality characteristics and flavor volatiles of Lueyang black-bone chicken meatballs cooked via different methods - Su, Wen; Zhao, Shibo; Zhou, Jinfeng; Xi, Linjie; Jin, Wengang; Abd El-Aty, A. M. (Frontiers in Nutrition, 2025)
Chicken meatballs are well received by consumers. This study evaluated the physicochemical properties and sensory attributes of Lueyang black-bone chicken meatballs prepared via three different cooking methods—steaming, boiling, and frying—and further analyzed their volatile compound profiles via gas chromatography–ion mobility spectrometry (GC–IMS). Compared with the steamed and boiled samples, the fried meatballs presented the highest sensory scores and greater hardness, adhesiveness, and chewiness (p < 0.05). Moreover, the color parameters [L*(34.67 ± 1.63), a*(6.89 ± 0.07), b*(15.12 ± 0.79)] of the fried samples differed notably from those of the other samples (p < 0.05), indicating the effect of thermal processing on their appearance. A total of 42 volatile organic compounds (VOCs), primarily ketones (31.92–47.55%), acids (17.57–24.33%), and esters (8.53–16.67%), were identified. OPLS-DA with VIP analysis (VIP > 1.0, p < 0.05) revealed 17 differential VOCs, with (E)-3-hexen-1-ol, hexanal, and ethyl 2-methylpropanoate significantly upregulated in fried samples (log2FC > 1). Overall, fried Lueyang black-bone chicken meatballs presented more favorable quality attributes. These results may offer valuable insights for the value-added development of Lueyang black-bone chicken meatball products.